Use of Matrix‐Assisted Laser Desorption Ionization Time‐of‐Flight Mass Spectrometry for the Identification of Pathogenic Vibrio in Fish. Issue 4 (23rd October 2018) - Burbick, Claire R.; Nydam, Seth D.; Hendrix, G. Kenitra; Besser, Thomas E.; Diaz, Dubraska; Snekvik, Kevin
Abstract: Matrix‐assisted laser desorption ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) is a rapid, cost‐effective method for identification of a broad range of bacterial taxa, but its accuracy for Vibrio spp. from samples of aquatic animal origin is unknown. We used DNA sequence analysis targeting two conserved genes, rpoB and rpoD, as the identification standard for 5 reference strains and 35 Vibrio spp. field isolates obtained from diagnostic aquaculture samples. Overall, MALDI‐TOF MS correctly identified 100% of the five reference strains to the genus level and 80% (4 of 5) to the species level. For field isolates, 83% (29 of 35) were correctly identified to the genus level, and 49% (17 of 35) were correctly identified to the species level. Eight (23%) field isolates were incorrectly identified at the species level. The MALDI‐TOF MS method produced no identification for 17% (6 of 35) of the field isolates. Using traditional culture identification, 100% of the five reference strains were correctly identified to the species level. All 35 field isolates were correctly identified to the genus level; 51% (18 of 35) of the isolates were identified correctly to the species level, while 29% (10 of 35) were misidentified at the species level. Overall, MALDI‐TOF MS was comparable to phenotypic identification, and accuracy will likely improve with enhancement of MALDI‐TOF MS database robustness.